Gravitational collapse to higher dimensional topological black holes - Mena, Filipe C. (2012)
We summarize recent results about the study of higher dimensional gravitational collapse to topological black holes. In particular, we considered models with interiors given by classes of 5-dimensional collapsing solutions built on Riemannian Bianchi IX spatial metrics and we proved local existence and uniqueness of radiating exteriors given by the Bizon-Chmaj-Schmidt metric.